Pengaruh Fasilitas Sekolah Terhadap Minat Belajar Siswa SMA Muhammadiyah Maumere - Bura, Trisnawati; Maria Eka Febriyanti Dua Dala; Magdalena Nona Irmin; Abdul Fizal; Yuni Frisanti Degu Bora (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the impact of school facilities on students' learning interest at SMA Muhammadiyah Maumere. The research employs a qualitative approach with a case study design, involving in-depth interviews and observations. The research respondents consist of 10 students from grades XI and XII, as well as one school principal. The results indicate that adequate facilities, such as comfortable classrooms, complete laboratories, and sufficient libraries, have a positive influence on students' learning interest. Supportive facilities enhance students' motivation and comfort during the learning process. This study also highlights the importance of teacher support and parental involvement in boosting students' learning interest. Based on the results and discussions, it can be concluded that school facilities significantly impact students' learning interest at SMA Muhammadiyah Maumere. Comfortable and complete facilities can enhance students' motivation and satisfaction, although there are still complaints regarding the fulfillment of needs and inadequate maintenance of facilities. Additionally, limited extracurricular activities focused on one type can make students feel compelled, indicating a need for variety in activity options. While facilities play an important role, support from teachers and parental involvement are also crucial in enhancing learning interest. Therefore, the school is advised to pay attention to improving facilities as well as other aspects that support a holistic learning experience for students.